Searches for long-lived charged particles in pp collisions at √s=7 and 8 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (SPRINGER, 2013)
Results of searches for heavy stable charged particles produced in pp collisions at root s = 7 and 8 TeV are presented corresponding to an integrated luminosity of 5.0 fb(-1) and 18.8 fb(-1), respectively. Data collected with the CMS detector are used to study the momentum, energy deposition, and time-of-flight of signal candidates. Leptons with an electric charge between e/3 and 8e, as well as bound states that can undergo charge exchange with the detector material, are studied. Analysis results are presented for various combinations of signatures in the inner tracker only, inner tracker and muon detector, and muon detector only. Detector signatures utilized are long time-of-flight to the outer muon system and anomalously high (or low) energy deposition in the inner tracker. The data are consistent with the expected background, and upper limits are set on the production cross section of long-lived gluinos, scalar top quarks, and scalar tau leptons, as well as pair produced long-lived leptons. Corresponding lower mass limits, ranging up to 1322 GeV/c(2) for gluinos, are the most stringent to date.
Keywords: Hadron-Hadron Scattering; HEAVY; SQUARK; Physics